Impact of the perceptual learning by simulation on decision making in volley ball, - Merzougue, Djamel; Abdedaim, Adda; Abed, Fouad; sebbane, Mohammed (My University, 2016)
The objective of this study is to approach the decision-making process in volley ball through the perceptual learning by simulation. 148 pupils took part voluntarily to this experience. The pupils were divided into two groups. An Experimental Group (EG) which was to follow a program of learning of the technics of the Volley Ball on computer (Images in 3D) before they begin the learning and a Control Group (CG) who performed the classical learning through technical exercises. Tests have been realized after a period of learning on different technics of volleyball. The results showed that the group experimental had significantly improved these results during the decision-making. This study shows the need to use the new technology (simulation) to optimize the mental skills in teaching volleyball.
Keywords: Perceptual learning - Simulation - Decision making - volley ball